2008
DOI: 10.1556/avet.56.2008.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Passive hip laxity in Estrela Mountain Dog — Distraction index, heritability and breeding values

Abstract: Two hundred and fifteen Estrela Mountain Dogs (EMD) were examined using the PennHIP method between 2002 and 2006. Passive hip laxity (PHL) was estimated calculating the distraction index (DI). Pedigree information was obtained from the Portuguese Kennel Club. The heritability and breeding values were estimated using the linear Animal Model. The DI, using as reference the worst joint of each animal, ranged from 0.15 to 1.12 (0.55 ± 0.19). The PHL was equal in right and left sides, and was higher in females than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 15 publications
3
22
0
7
Order By: Relevance
“…Therefore, BV estimation can be used as an alternative procedure (Tellhelm 2007). The slight worsening of the ED genetic trend per year of birth (slight positive slope of tendency line) seems similar to the genetic trends in the same breed for passive hip laxity and hip dysplasia mentioned in previous studies (Ginja et al 2008(Ginja et al , 2009 When there exists a large genetic correlation between two traits, associated with a high and a low heritability for each trait, a potential increase in genetic progress is expected to occur in the trait with low heritability, when selecting for the other (Cachon et al 2010;Lewis et al 2011). Although showing differences between breeds, previous studies are suggestive of a positive genetic correlation between ED and hip dysplasia (Cachon et al 2010;Lewis et al 2011;Woolliams et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, BV estimation can be used as an alternative procedure (Tellhelm 2007). The slight worsening of the ED genetic trend per year of birth (slight positive slope of tendency line) seems similar to the genetic trends in the same breed for passive hip laxity and hip dysplasia mentioned in previous studies (Ginja et al 2008(Ginja et al , 2009 When there exists a large genetic correlation between two traits, associated with a high and a low heritability for each trait, a potential increase in genetic progress is expected to occur in the trait with low heritability, when selecting for the other (Cachon et al 2010;Lewis et al 2011). Although showing differences between breeds, previous studies are suggestive of a positive genetic correlation between ED and hip dysplasia (Cachon et al 2010;Lewis et al 2011;Woolliams et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…A larger study by Zhang et al (2009) comprising 2,716 dogs across 17 breeds reported a heritability of 0.61 for the distraction index. A recent genetic analysis of the distraction index in the Estrela Mountain dog, using a linear animal model, reported a very high heritability of 0.83 (Ginja et al 2008). This estimate was based only on 215 observations and has an SE of 0.11.…”
Section: Soo and Worthmentioning
confidence: 99%
“…Selection on traits with heritabilities in this range can most definitely benefit from the use of EBVs. However, few breeding schemes have utilised EBVs for the control of CHD, although many authors have recommended EBV use [12]–[15] and have demonstrated the feasibility of EBVs for a variety of CHD scoring schemes [6], [14], [16][18]. The Seeing Eye Inc began using EBVs in 1995 and soon observed substantial reductions in radiographic signs of CHD [6].…”
Section: Introductionmentioning
confidence: 99%